2016
DOI: 10.1016/j.jecp.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s referent selection is guided by novelty for both words and actions

Abstract: Young children are biased to select novel, name-unknown objects as referents of novel labels and to similarly favor novel, action-unknown objects as referents of novel actions. What process underlies these common behaviors? In the case of word learning, children may be driven by a novelty bias favoring novel objects as referents. Our study investigated this bias further by investigating whether novelty also affects children's selection of novel objects when a new action is given. In a pre-exposure session, 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“…The longitudinal assessment of ME use across two ages presented in this study sheds light on the transition of ME from a default assumption in referent selection tasks, which is possibly grounded in general attentional biases (Dysart et al., ; Hollich et al., ; Pruden et al., ; Samuelson et al., ), to a sophisticated word‐learning assumption or strategy moulded by the child's individual lexical knowledge and linguistic experience. This dynamic view of ME has been postulated for monolingual infants (McMurray et al., ; Samuelson et al., ; Samuelson & McMurray, ), whereby their initial tendency to attend to a novel object when presented with a novel label, regardless of whether a familiar competitor is present or not (Horst et al., ; Mather & Plunkett, ), becomes more constrained with the growth of their specific (Grassmann et al., ) and abstract (Graham et al., ; Kalashnikova, Mattock et al., ) vocabulary knowledge.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The longitudinal assessment of ME use across two ages presented in this study sheds light on the transition of ME from a default assumption in referent selection tasks, which is possibly grounded in general attentional biases (Dysart et al., ; Hollich et al., ; Pruden et al., ; Samuelson et al., ), to a sophisticated word‐learning assumption or strategy moulded by the child's individual lexical knowledge and linguistic experience. This dynamic view of ME has been postulated for monolingual infants (McMurray et al., ; Samuelson et al., ; Samuelson & McMurray, ), whereby their initial tendency to attend to a novel object when presented with a novel label, regardless of whether a familiar competitor is present or not (Horst et al., ; Mather & Plunkett, ), becomes more constrained with the growth of their specific (Grassmann et al., ) and abstract (Graham et al., ; Kalashnikova, Mattock et al., ) vocabulary knowledge.…”
Section: Discussionmentioning
confidence: 84%
“…The capacity to reason by exclusivity in tasks testing the disambiguation effect has been ascribed to general attentional biases that are not specific to the process of lexical acquisition (Dysart, Mather, & Riggs, ; Hollich et al., ; Horst, Samuelson, Kucker, & McMurray, ; Samuelson, Kucker, & Spencer, ; Samuelson & McMurray, ). For example, infants as young as 10 months select novel instead of familiar objects in response to novel labels based on biases to attentionally salient (Pruden, Hirsh‐Pasek, Golinkoff, & Hennon, ) and novel objects (Mather & Plunkett, ).…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus in the literature to-date appears to be that, at later ages, from around 3 to 4 years, there are few differences in children’s ability to fast-map novel word-object and action-object associations [6, 13, 14]. Riggs, Mather, Hyde, and Simpson showed that a) 3- to 4-year-old children choose a novel object relative to a familiar object when presented with a novel action or a novel word, b) retain the action-object association and extend it to other members of the object category as they do with words, and c) distinguish between a previously familiarized novel-action-object mapping and an unfamiliar novel-action-object mapping, showing that they had formed a detailed representation of the novel action presented [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that exclusion learning is controlled by rejection of the defined comparison stimulus (e.g., Dixon, 1977;Horst, Scott, & Pollard, 2010;Markman et al, 2003). There is also evidence that participants relate the undefined sample and comparison on the exclusion trials based on novelty (Dysart, Mather, & Riggs, 2016). Further, both kinds of control can simultaneously influence exclusion-task performance (Wilkinson & McIlvane, 1997).…”
Section: Discussionmentioning
confidence: 99%